A review on the socio-demographic and cultural factors associated with the delayed diagnosis of cervical cancer and possible interventions in screening attitude: From South Asian perspective - Tarannum, Nafisa; Binte Ismail Eva, Ismat Ara (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.